PEMBENTUKAN KARAKTER SISWA MELALUI PENGEMBANGAN KURIKULUM MUATAN LOKAL ASWAJA - Fatkhul Khamid; Hamdan Adib (Prodi PAI Sekolah Tinggi Agama Islam Serdang Lubuk Pakam, 2021)
Curriculum development is something that must be done by educational institutions, especially in relation to curriculum development in an effort to form the character of students who respect each other even though they have different understandings. This study aims to determine the implementation of the Aswaja religious local content curriculum in shaping the character, constraints and supporting factors faced by teachers in implementing the curriculum. The research method used is qualitative with the type of field research. The data sources are school principals, waka curriculum and local content teachers aswaja. Data were collected using interview, observation and documentation techniques. The results of this study are first, the implementation of the Aswaja religious mulok curriculum in an effort to build the character of students based on moral intelligence in MA Nurul Islam Kriyan Aswaja learning does not refer to theory only, but also through the application of habits in madrasas, this is a conscious and continuous effort in introduce and instill the basic values ​​of Aswaja in students. second, the obstacles faced are the limited availability of textbooks, inadequate facilities and infrastructure, limited time for teachers to teach, and lack of student interest. Third, the supporting factors are the teachers and the madrasa culture with the nuances of aswaja